CHINA'S ECONOMIC CYBER STRATEGY IN FACING ECONOMIC CYBER THREATS 2020 - 2023 - Putri, Sylvia Octa; Farras S, Hanna Tri Indah; Rachman, Dio Fathul; Septiana, Intan Fauzi; Sihombing, Jerry Yeremiah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Digital technology has succeeded in making it easier for a country to analyse data, development, improvement of a performance or product which is then included in a network. These advances in digital technology also have a risk impact on security issues. This research examines the cybereconomic strategy applied by China in dealing with the threat of economic cybers between 2020 and 2023. With the rapid growth of information technology, China faces significant challenges in ensuring its economic cybersecurity. This research analyses the steps taken by the Chinese government to address economic cyber threats, including increased regulation, investment in cybersecurity, and cyber diplomacy efforts. In this study the researcher uses a qualitative method. Qualitative method is a research or observational procedure that produces descriptive data that emphasizes the concept of a problem in research. The findings suggest that China has adopted a comprehensive and proactive approach to protecting its economic cybersecurity, although it still faces significant challenges. The implication of this research is the importance of technological innovation in overcoming economic cyber threats in the era of digital globalization.